A bibliometric analysis and visualization of tension-type headache - Fan, Xueming; Fu, Guojing; Wang, Liuding; Shen, Wei; Zhang, Yunling (Frontiers in Neurology, 2022)
Background: Tension-type headache (TTH) is the most prevalent headache in the clinical practice, leading to impaired social activities, work-related disability, and heavy financial burdens. Previous studies have described possible inducement, potential pathophysiology and clinical management of TTH; however, due to the lack of attention, literature involving bibliometric analysis is sporadic. Therefore, this study aimed to explore the current hotspots and future directions of TTH field by bibliometric analysis. Methods: By using CiteSpace and VOSviewer, literatures regarding TTH between 2002 and 2021 from Web of Science database were summarized and extracted. Annual publication trend, the most productive countries/regions and institutions, distribution of categories, co-citation of journals and references, and co-occurrence of keywords were analyzed. Results: A total of 3379 publications were included in the final visualization, indicating a stable trend in current research and a lack of breakthroughs over the past decades. These studies were mainly conducted in 120 countries/regions led by the United States and more than 600 institutions. Four eternal core themes were identified in TTH, including neurosciences, nursing, developmental psychology, and general/internal medicine. Cephalalgia ranked first, with the highest number of literatures, and is the most influential journal in this area. Keywords analysis demonstrated that the similarities and differences between migraine and TTH, epidemiological studies, clinical double-blind trials, and potential populations have become key issues in the TTH field. Conclusion: TTH has received less attention and breakthroughs in the past 20 years. To promote coordinated development between regions to fight headaches, cooperation and exchanges between countries and institutions are essential in the future. Relevant studies about headaches in children and adolescents, inducing factors such as emotional triggers and sleep disorders, concomitant diseases, possible pathogenesis, and headache treatments are in the spotlight in recent years. This study offers a powerful roadmap for further research in this field.